Development of a HOTS-based Multiple Choice Question Test Instrument on the Basic Competency of Understanding Marriage Provisions According to Legislation - Thowiyyah, Husni; Hidayatulloh, Muhammad Kris Yuan (APPLICATION: Applied science in Learning Research, 2024)
This research aims to develop and test a test instrument based on Higher Order Thinking Skills (HOTS) in the form of multiple choice questions, as well as analyzing students' higher order thinking abilities and their responses to this instrument. The method used is Research & Development with the Rudi Hari Rayanto and Sugiati development model using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) approach. The research subjects were 20 students of class XI MIPA at MA Bahrul Ulum Tambakberas Jombang. The validation results show an average validation rate of 90%, indicating a good match rate. Of the 40 questions developed, all were declared feasible with a calculated r value > r table (0.3291) and a reliability of 1.00 > 0.75, indicating high reliability of the questions. The difficulty of the questions is medium average, with 8 questions having a high level of difficulty. Question distractors were also effective, with the number of students choosing the answer option exceeding 5% of the total number of students. The trial results showed that students' high-level thinking abilities were at medium criteria, and students' responses to this instrument reached 80%, indicating a positive response to its use in learning. Thus, it can be concluded that the test instrument developed is suitable for use in a learning context, contributing to the good measurement of students' higher-level thinking abilities.